Aerothermodynamics analysis of a reentry vehicle with surface discontinuity-like a gap - Luis Thiago Lucci Corrêa Paolicchi (2017)
A computational analysis has been performed in order to investigate the impact of the presence of gaps and variations on the vehicle nose radius in the flowfield structure, as well as on the aerodynamic properties of hypersonic vehicles in atmospheric reentry at different altitudes. The calculations were performed with a computational model that takes into account the effects of thermodynamic non-equilibrium. A detailed description of the impact on the flow structure - velocity, density, pressure and temperature - as well as on aerodynamic properties - number flux, heat transfer, pressure and skin friction - is presented for various sections of the vehicle due to variations in the gap ratio (L/H) and nose ratio (R), for altitudes (A) of 100, 90 and 80 km. For the conditions investigated, the analyzes showed that the gap presence caused a small influence on the flowfield structure and that a single vortex inside the gap for all gap ratio (L/H) investigated was formed, thus demonstrating that the flow topology inside the gap for transition flow regime differs from the flow topology present for the continuum flow regime. In addition, as the vehicle becomes more aerodynamic, i.e., with the decrease in vehicle nose radius (R), disturbances in the flow structure around the vehicle are smaller and larger are the heat and pressure loads inside the gap.